Ethnobotany of Amorphophallus muelleri var. Madiun I: Culture and Nutraceutical Study in Klangon Village of Madiun Regency, Indonesia - Widya Kristiyanti Putri; Didik Pudji Restanto; Nisrina Qonitah (Jurnal Ilmu Lingkungan, 2025)
Klangon Village, Saradan District in Madiun Regency is one of the largest porang-producing villages in Indonesia with export quality results, making it one of the Porang Center villages. Porang cultivation is believed to have been carried out from generation to generation in an agroforestry system. This study aims to reveal more about the role of porang for the people of Klangon Village, both in terms of culture and its relationship to the phytochemical content of porang. The study was conducted through observation, ethnobotanical data collection, phytochemical data collection as nutraceuticals, and data analysis. Phytochemical data was collected using spectrophotometry while spatial data was collected using the GPS Essentials application. Ethnobotanical analysis was carried out using the Cultural Significance Index (CSI). Nutraceutical analysis by testing the content of vitamins using the spectrophotometric method. It was concluded that Ethnobotanical studies of porang plants show the highest CSI values in porang plants and nutraceutical studies of porang show the content of antioxidants (vitamin E), vitamins B1, and B6.